Political philosophy : the essential texts - Cahn, Steven M. (New York : Oxford University Press, 2015)
"Now greatly expanded in its third edition, Political Philosophy: The Essential Texts is ideal for survey courses in social and political philosophy. Offering coverage from antiquity to the present, this historically organized collection presents the most significant works from nearly 2,500 years of political philosophy. The readings are substantial or complete texts, not fragments. An especially valuable feature of this volume is that the works of each author are introduced with an engaging essay by a leading contemporary authority. Political Philosophy moves from classical thought (Plato, Aristotle, Cicero) through the medieval period (Augustine, Aquinas) to modern perspectives (Machiavelli, Hobbes, Spinoza, Locke, Montesquieu, Rousseau, Hume, Adam Smith, Kant, Hamilton and Madison, Burke, Bentham, Tocqueville). The book includes work from major nineteenth-century thinkers (Hegel, Marx and Engels, Mill, Nietzsche) and twentieth-century theorists (Arendt, Hayek, Berlin, Taylor, Rawls, Sandel, Nozick, Foucault, Habermas, Held, Nussbaum, Young, Appiah) and also presents a variety of notable documents and addresses in a separate section, including The Declaration of Independence and speeches by Abraham Lincoln, John Dewey, and Martin Luther King, Jr. In addition to the new selections noted above in bold, the third edition also includes the complete text of Mill's On Liberty, an excerpt from Rawls's Political Liberalism, and reedited selections from Plato, Aristotle, Machiavelli, Hobbes, Locke, and The Federalist Papers"--
Keywords: Political science -- Philosophy -- Textbooks; PHILOSOPHY / Political